Structural Model of Marital Conflict Based on Self-Differentiation and Alexithymia with the Mediating Role of Frustration Tolerance in Divorce-Seeking Individuals - Hosseini, Samira; Mousavi, Said Ali mohammad; Shomalyoskoei , Arezoo (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the structural model of marital conflict based on self-differentiation and alexithymia with the mediating role of frustration tolerance in individuals seeking divorce. This study was fundamental in purpose and descriptive-correlational in design. The statistical population consisted of all divorce-seeking individuals who referred to family counseling centers affiliated with the judiciary in Karaj and Hashtgerd between February 2025 and October 2025. A sample of 250 participants (139 women and 111 men) was selected using convenience sampling and completed the research instruments voluntarily. Data were collected using the Marital Conflict Questionnaire (Sanaei et al., 2008), the Self-Differentiation Inventory (Skowron & Friedlander, 1998), the Toronto Alexithymia Scale (Bagby et al., 1994), and the Frustration Discomfort Scale (Harrington, 2005). Data analysis was conducted using Structural Equation Modeling (SEM) with SPSS version 27 and AMOS version 26 through Maximum Likelihood estimation. Model fit was evaluated using standard fit indices including χ²/df, GFI, AGFI, CFI, and RMSEA. The results indicated that the proposed structural model demonstrated acceptable fit with the data (χ²/df = 1.67, CFI = 0.94, RMSEA = 0.05). Alexithymia had a positive and significant direct effect on marital conflict (β = 0.206, p < .05), whereas self-differentiation had a negative and significant direct effect (β = -0.276, p < .01). Frustration tolerance significantly predicted marital conflict (β = 0.431, p < .001) and also mediated the relationships between alexithymia and marital conflict (β = 0.167, p < .001) and between self-differentiation and marital conflict (β = -0.156, p < .001). The model explained 55% of the variance in marital conflict (R² = 0.55). The findings suggest that alexithymia and self-differentiation play significant roles in predicting marital conflict both directly and indirectly through frustration tolerance, highlighting the importance of emotional processing and coping capacity in marital dynamics and offering implications for targeted psychological interventions.